Anthropomorphic Phantoms for Confirmation of Linear Accelerator-Based Small Animal Irradiation - Perks, Julian R (Cureus, 2015)
Three dimensional (3D) scanning and printing technology is utilized to create phantom models of mice in order to assess the accuracy of ionizing radiation dosing from a clinical, human-based linear accelerator. Phantoms are designed to simulate a range of research questions, including irradiation of lung tumors and primary subcutaneous or orthotopic tumors for immunotherapy experimentation. The phantoms are used to measure the accuracy of dose delivery and then refine it to within 1% of the prescribed dose.